2021
DOI: 10.1002/csc2.20504
|View full text |Cite
|
Sign up to set email alerts
|

Seeding depth effects on elongation, emergence, and early development of California rice cultivars

Abstract: The continuous use of a water‐seeded cropping system for California rice (Oryza sativa L.), along with a limited palette of available herbicides, have selected for flood‐tolerant grasses, aquatic species, and herbicide‐resistant weed populations throughout the region. Alternative cropping methods such as stale‐seedbed and deeper drill seeding may be combined to allow novel herbicide modes of action and combat resistance while providing economically competitive yields. Two experiments were conducted to evaluate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…Koger et al (2006) observed cultivar differences in pendimethalin applications on long-grain rice in a dry-seeded system. Relative tolerance was attributed to the mesocotyl length of seedling rice, which may vary by cultivar; however, planting depth is also an important factor in dry-seeded rice for achieving pendimethalin tolerance (Ceseski and Al-Khatib 2021; Ceseski et al 2022; Koger et al 2006). In water-seeded rice, a mesocotyl is not present on seedlings because the seeds are placed on the soil surface; however, differences in seedling vigor can be important for relative tolerance to pendimethalin.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Koger et al (2006) observed cultivar differences in pendimethalin applications on long-grain rice in a dry-seeded system. Relative tolerance was attributed to the mesocotyl length of seedling rice, which may vary by cultivar; however, planting depth is also an important factor in dry-seeded rice for achieving pendimethalin tolerance (Ceseski and Al-Khatib 2021; Ceseski et al 2022; Koger et al 2006). In water-seeded rice, a mesocotyl is not present on seedlings because the seeds are placed on the soil surface; however, differences in seedling vigor can be important for relative tolerance to pendimethalin.…”
Section: Resultsmentioning
confidence: 99%
“…In water-seeded rice, a mesocotyl is not present on seedlings because the seeds are placed on the soil surface; however, differences in seedling vigor can be important for relative tolerance to pendimethalin. Ceseski and Al-Khatib (2021) observed that the M-205 and M-209 cultivars had greater seedling vigor than M-105 and M-206, when drill-seeded in a high-clay soil. Additionally, S-102 is a short-grain, very early maturing cultivar (fewer than 80 d to 50% heading) and higher cold temperature tolerance than other common short- and medium-grain rice cultivars (McKenzie et al 1997).…”
Section: Resultsmentioning
confidence: 99%
“…The increase in coleoptile length before emergence is the most critical indicator of seedling establishment. A recent study has shown that deep seed sowing affects coleoptile growth, and thus the seedlings fail [33]. Kimmelshue and colleagues stated that one of the major problems facing agriculture programs in the Sahel is sowing depth, which imposes high soil pressure during seed germination and shoot up-thrust [34].…”
Section: Introductionmentioning
confidence: 99%